PELAKSANAAN PEMBERDAYAAN UED-SP BINA MANDIRI SERTA UPAYA PENGEMBALIAN MODAL PINJAMAN DI DESA TELUK LANCAR KECAMATAN BANTAN KABUPATEN BENGKALIS TAHUN 2011-2013 - Beriy anggoro; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Community empowerment is an attempt to show the state or the results to be achieved by an empowered community of social change , have power or control in meeting the search , participate in social activities and independent in carrying out their needs whether physical , economic , and social as having confidence , as well as the expression of aspiration , has eyes the tasks of life . It would also require a supporting factor in terms of education , health and social culture . The purpose of this study was to determine the causes of the ineffectiveness of Rural Development Program in Business Economics - Village Savings and Loans ( UED - SP ) in the District of Bantan Current Teluk Bengkalis Year 2011-2013 . As for the background of this research is the ineffectiveness of the Village Empowerment Program in Current Bay Village this well . The large number of delinquent loans funds user community UED - SP , where Fluent BayVillage is the largest village arrears of Villages in the District Bantan Bengkalis.This study belongs to the type of qualitative research , using data collection techniques with in-depth interviews to respondents who have been assigned . Respondents were chosen consists of an element of empowerment programs and also from elements of the user community funds .Based on the research that has been done with the author , it can be seen that the lack of effectiveness in the implementation of rural development programs in DesaTeluk Current. Most of the program is running smoothly , but at the end of this program was limited to payback the loan or delinquent . Less stringent system in an effort to foreclosure of collateral that because many of the beneficiaries were relatives of staff UED - SP . Lack of partnership between the public administration , the system is too rigid , and the lack of programs that reflect the mutual cooperation in solving the problems of arrears . Beneficiaries have not been fully able to manage loan well .Keywords : empowerment , human resources and UED - SP Bina Mandiri.